Interpretação neuro-simbólica de vídeo em ambiente de futebol - Silva Neto, Odalisio Leite da (Brasil, 2024)
This term paper presents an approach to interpreting soccer videos using tensor logic. The overall objective is to automate the extraction and interpretation of soccer skills to facilitate the analysis of athlete development in schools. The result was a system capable of identifying class and ball possession with at least 90% accuracy. The technology can be applied in areas other than soccer.